Revolutionizing Training in Continuing Engineering Education: An Experimental Proposal Using the Multi-Sensory Virtual Decision-Making Center - Jose Daniel Azofeifa; Valentina Rueda-Castro; Luis Jose Gonzalez-Gomez; Julieta Noguez; Patricia Caratozzolo (IEEE Access)
In the context of Industry 4.0, engineering education is evolving rapidly, requiring new approaches to continuing engineering education (CEE). Traditional methods struggle to meet the demands of professionals looking to update their skills. This study presents an experimental proposal using the Multisensory Virtual Decision Making Center (MVDC) to improve CEE training creation. The MVDC creates collaborative and immersive virtual environments, enabling real-time participation and decision-making with a greater sense of presence and complete data visualization. The proposed experiment compares the effectiveness of MVDC sessions with traditional video call sessions in developing CEE courses. The research aims to evaluate improvements in the quality of decisions, participation, and user satisfaction in this collaborative process by streamlining the training planning process for continuing education. This study anticipates significant insights into integrating cutting-edge technologies such as MVDC for CEE, proposing it as a crucial tool for upskilling and reskilling. Expected outcomes include practical guidelines for implementing multisensory environments in CEE curriculum development, highlighting their potential to revolutionize the planning process. The research underscores the need for innovative approaches to meet the changing demands of the engineering workforce in the era of Industry 4.0. It lays the foundation for future studies that validate and expand these findings, paving the way for more effective and engaging CEE programs.